2017
DOI: 10.11606/s1518-8787.2017051007139
|View full text |Cite
|
Sign up to set email alerts
|

Access to medicines by patients of the primary health care in the Brazilian Unified Health System

Abstract: OBJECTIVE To evaluate the access to medicines in primary health care of the Brazilian Unified Health System (SUS), from the patients’ perspective.METHODS This is a cross-sectional study that used data from the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Services, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines), conducted by interviews with 8,591 patients in cities of the five regions of Brazil. Evaluation of access to medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 14 publications
1
23
0
15
Order By: Relevance
“…Our study found an increased lack of access to treatments when compared to a population-based study conducted in Porto Alegre, Southern Brazil with 2,988 individuals in 2003, which found that 5% of the participants who used medicines in the 15 days prior to the interview could not obtain appropriate treatment ( Bertoldi et al., 2009 ). Previous data from population-based studies reinforce the differences in the access to treatments between Brazilian regions, particularly in the North and Northeast regions, the least developed of the country ( Paniz et al., 2008 ; Goes et al., 2016 ; Alvares et al., 2017 ).…”
Section: Discussionmentioning
confidence: 73%
“…Our study found an increased lack of access to treatments when compared to a population-based study conducted in Porto Alegre, Southern Brazil with 2,988 individuals in 2003, which found that 5% of the participants who used medicines in the 15 days prior to the interview could not obtain appropriate treatment ( Bertoldi et al., 2009 ). Previous data from population-based studies reinforce the differences in the access to treatments between Brazilian regions, particularly in the North and Northeast regions, the least developed of the country ( Paniz et al., 2008 ; Goes et al., 2016 ; Alvares et al., 2017 ).…”
Section: Discussionmentioning
confidence: 73%
“…Na forma de admissão do usuário com hanseníase no CSEM, destacou-se o modo de entrada do tipo caso novo, perfazendo-se, desta forma, a Atenção Primária em Saúde como a primeira porta de entrada aos serviços do Sistema Único de Saúde (ALVARES, 2017).…”
Section: Discussionunclassified
“…130 In Brazil, the list of essential drugs has been reported to include discrepancies between the WHO recommendations and the drugs included in the Brazilian National Relation of Essential Medicines, [131][132][133][134][135][136] as well as, that there is low availability of essential medicines in public health units. 137 Because the list is not even in use in most LatAm countries, investigators are encouraged to verify if the essential drug list is up to date and to validate the list prior to implementing any DUR studies.…”
Section: Specific Challenges Facing Dur In Latammentioning
confidence: 99%